Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1080/10903120802472012
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Helicopter Emergency Medical Services Dispatch Criteria for Traumatic Injuries: A Systematic Review

Abstract: Only 5 studies described HEMS dispatch criteria validity. HEMS dispatch based on consciousness criteria seems promising. MOI criteria lack accuracy and will lead to significant overtriage. The first categories needing revision are MOI and age/comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 50 publications
6
56
0
Order By: Relevance
“…This result may indicate a lower threshold for responding to trauma than to medical emergencies. The initial phase after an accident is often characterized by uncertainty, which may contribute to over‐triage in HEMS, as others have reported 23. A number of rescued hikers and skiers who sustain relatively minor trauma also reduced the median NACA for trauma patients in the current study.…”
Section: Discussionsupporting
confidence: 53%
“…This result may indicate a lower threshold for responding to trauma than to medical emergencies. The initial phase after an accident is often characterized by uncertainty, which may contribute to over‐triage in HEMS, as others have reported 23. A number of rescued hikers and skiers who sustain relatively minor trauma also reduced the median NACA for trauma patients in the current study.…”
Section: Discussionsupporting
confidence: 53%
“…28 Many laudable attempts to streamline prehospital trauma triage have attempted to identify anatomic, physiologic, or situational components that identify patients appropriate for advanced trauma care without resulting in substantial overtriage. [29][30][31] Reliance on physiologic criteria/vital signs alone, for instance, will likely result in unacceptable levels of undertriage, as patients with significant injuries may have normal vital signs at the scene. 32,33 The same concerns apply to triage decisions based solely on anatomic or situational factors.…”
Section: Use Of the Cdc 2011 Guidelines For The Field Triage Of Injurmentioning
confidence: 99%
“…32,33 The same concerns apply to triage decisions based solely on anatomic or situational factors. 31,34,35 The strength of evidence addressing patient morbidity and mortality associated with field triage decisions was judged to be low, largely due to the lack of prospective, large-scale trials. The prospective data that do exist are derivation studies or pilottesting of new triage parameters, such as heart-rate variability.…”
Section: Use Of the Cdc 2011 Guidelines For The Field Triage Of Injurmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the data needed to improve the accuracy of these criteria and better align urgent resources with the needs of patients are limited. In a recent systematic review of criteria for dispatch of air transport for severely injured patients, Ringburg and colleagues 6 found that the validity of the criteria varied widely. They noted, for instance, that 22 of 49 discrete launch criteria were driven primarily by reported mechanism of injury.…”
mentioning
confidence: 99%